STRATEGI PEMERINTAH KOTA BATU MEMPERTAHANKAN UMKM DI MASA PANDEMI COVID-19 DALAM UPAYA PEMULIHAN EKONOMI MASYARAKAT - Sopiana, Natalia; Sasmito, Cahyo; Hardianto, Willy Tri (Jurnal Ilmiah Publika, 2022)
The results of the Batu City Government Strategy related to the existence of goals and targets have been implemented quite well. Through MSMEs and Cooperatives and City trade, as for the efforts made by the Batu City government, namely government policies for MSMEs in the midst of the Covid-19 pandemic, including the provision of financial assistance to capital loan relief, as for this type of research using a qualitative descriptive method as will be adapted The problems are generally divided into two types, namely qualitative and quantitative research. The focus of this research is an act of utilizing the barrier which is related to the object to be studied. The data that will be used in this research are primary and secondary data, the technique of determining the informants is using purposive sampling technique. In this research, data collection techniques can be classified into several parts, including: documentation, observation and interviews. The data analysis technique used is data reduction, data display to drawing conclusions (Conclusion Drawing/Verification). Batu City, namely the Batu City government, continues to provide training related to the allocation of a resource that can be used properly, so that the Micro, Small and Medium Enterprises will continue to survive in the Corona Virus situation, such as the time and the participation of the MSME community as well as the allocation of funds or funds. help. And while the inhibiting factor is that many souvenir places and tourist attractions are closed.